Ukuran Bank Memoderasi Pengaruh CAR, NPL dan BOPO Terhadap Profitabilitasa - Riki Saputra; Batara Daniel Bagana (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), and Operating Costs on Operating Income (BOPO) on Return on Assets (ROA) with Firm Size as a moderating variable in Conventional Commercial Banks for the period 2019 to 2024. The study uses a quantitative approach with secondary data obtained from the annual financial statements of banking companies. The research sample consists of 20 Conventional Commercial Banks selected using a purposive sampling technique to obtain 120 company-year observations. Data analysis was performed using multiple linear regression with the help of Eviews13. The results showed that CAR had no effect on ROA with a coefficient value of -0.014103 and a probability of 0.0618 (>0.05). NPL and BOPO had a significant negative effect with coefficients of -0.140604 and -0.067983 with probability values ??of 0.0002 and 0.0000 (<0.05), respectively. Meanwhile, Firm Size is only able to moderate the influence of NPL and BOPO but does not moderate the influence of CAR on ROA. Firm Size strengthens the negative influence of NPL on ROA and Firm Size weakens the negative influence of BOPO on ROA, the interaction coefficient value of NPL and Firm Size is -0.052218 and a probability value of 0.0121 (<0.05). While the interaction coefficient value between BOPO and Firm Size is 0.005858 with a probability of 0.0062 (<0.05). The results of simultaneous testing with the Goodness of Fit test obtained a probability result of 0.0000 below 0.05 which indicates that CAR, NPL and BOPO simultaneously influence ROA. This finding indicates that these variables are very important in influencing bank profitability. This study provides a theoretical contribution by expanding the empirical evidence that the application of Signaling theory and Agency Theory in explaining the influence of CAR, NPL and BOPO on ROA. In addition, this study provides a methodological contribution through the use of the coefficient of variation as the level of capital adequacy, the level of credit risk and operational efficiency in Conventional Commercial Banks with firm size as a moderating variable, as well as providing a practical contribution as a reference for management and investors in evaluating financial performance that affects profitability.